Early growth and death from cardiovascular disease in women. Issue 6918 (11th December 1993) - Osmond, C; Barker, D J; Winter, P D; Fall, C H; Simmonds, S J
Abstract : OBJECTIVE–To determine whether the link suggested between growth in utero and during infancy and death from cardiovascular disease in men is also present in women. DESIGN–Follow up study of women and men whose birth weight and weight at 1 year of age had been recorded. SETTING–Hertfordshire, England. SUBJECTS–5585 women and 10, 141 men born during 1911-30. MAIN OUTCOME MEASURES–Standardised mortality ratios for cardiovascular disease. RESULTS–Among women and men death rates from cardiovascular disease fell progressively between the low and high birth weights groups (chi 2 = 4.3, p = 0.04 for women, chi 2 = 8.5, p < 0.005 for men). Cardiovascular deaths in men but not women were also strongly related to weight at 1 year, falling progressively between the low and high weight groups (chi 2 = 27.5, p < 0.0001). The highest cardiovascular death rates in women were among those with below average birth weight but above average weight at 1 year. In men the highest rates were among those with below average birth weight and below average weight at 1 year. CONCLUSION–Relations between cardiovascular disease and birth weight are similar in men and women. In men cardiovascular disease is also related to weight gain in infancy.